Analysis of wind energy demand and supply scenarios for the triennium 2021-2023: comparisons with the PNE 2050 - Brito Muniz, Giselle Francine; Moura dos Santos Miranda, Bruno; Barreto Montenegro, Estefani Maria; Souza Pinto, Jonas; Medeiros Gomes de Oliveira, Anna Maria; Oliveira da Silva, Joseane (Latin American Journal of Energy Research, 2024)
Wind energy gained prominence on the national scene as a renewable source, with significant cooperation in the Brazilian energy matrix in the last decade. With regard to the energy planning process, the National Energy Plan (PNE 2050), published in 2020, emerges as an initiative capable of defining the trajectories and goals for the transformation of the Brazilian energy sector, which includes the demand, supply and financial contribution scenarios provided by wind power generation. To this end, the methodology used was qualitative and quantitative, based on official data, current public policies, specialized doctrine and technical documents published by the official agencies of the Brazilian energy regulatory sector. On this basis, this paper explores the scenarios involving wind energy in Brazil from 2021 to 2023. The development of the contribution of wind power sources is in a positive context, with percentage growth higher than expected, and the annual increases were the highlights with the highest percentages of variation, although the officialization of regulatory frameworks and challenges will require subsidies in the coming decades.